Local educational order : enthnomethodological studies of knowledge in action - Hester, Stephen; Francis, D. W. (Pragmatics & beyond, 2000)
The studies in this book take an ethnomethodological approach to educational phenomena. Ethnomethodology's concern is with the locally accomplished and situated character of social order. With reference toeducational phenomena, this means that ethnomethodology investigates how the 'natural facts' of educational life, such as daily activities in school classrooms, are produced as such in the first place, rather than taking forgranted the recognisability of these facts and then theorising their explanation. In this sense, ethnomethodological studies contrast markedly with other approaches to the.